2022
DOI: 10.1186/s13048-022-01021-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 signaling regulates cytokines and chemokines expression and secretion in granulosa cell

Abstract: Background Granulosa cells (GCs) are multilayered somatic cells within the follicle that provide physical support and microenvironment for the developing oocyte. In recent years, the role of Neuregulin-1 (NRG1), a member of the EGF-like factor family, has received considerable attention due to its neurodevelopmental and cardiac function. However, the exact physiological role of NRG1 in GC is mainly unknown. In order to confirm that NRG1 plays a regulatory role in rat GC functions, endogenous NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Furthermore, inflammatory pathways are altered or inactivated by exogenous NRG1 treatments related to the tissue damage during ischemic episodes [61][62][63]. It was recently reported that cytokines and chemokines expression and secretion are regulated by NRG1 signaling [69]. Besides, Nedd4l-mediated downregulation of NRG1 plays a vital role in mice's depression-like phenotypes in chronic social defeat stress [70], in line with our outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, inflammatory pathways are altered or inactivated by exogenous NRG1 treatments related to the tissue damage during ischemic episodes [61][62][63]. It was recently reported that cytokines and chemokines expression and secretion are regulated by NRG1 signaling [69]. Besides, Nedd4l-mediated downregulation of NRG1 plays a vital role in mice's depression-like phenotypes in chronic social defeat stress [70], in line with our outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…In the ovary, Nrg1 expression in granulosa cells is induced by LH. Studies using Nrg1-knockdown and exogenous Nrg1 treatment showed the gonadotropins-dependent Nrg1 signaling in granulosa cells is important for supporting follicular growth and oocyte meiotic maturation [210]. Consistently, targeted disruption of Nrg1 in granulosa cells of gcNrg1KO mice reduces the number of pups per litter, perhaps due to aberrant regulation of protein kinase C signaling in cumulus cells [211,212].…”
Section: Ovarian Surface Cutting Improves Follicular Development In A...mentioning
confidence: 89%
“…Increased NRG1 expression can activate downstream signaling pathways, such as the ERBB2/ ERBB3 pathway, which promotes cancer cell proliferation, migration, and survival (12). Notably, NRG1 expression can be modulated by various factors, including growth factors, hormones, and environmental stimuli (13)(14)(15)(16). Dysregulation of NRG1 expression can occur through genetic alterations, epigenetic changes, or altered transcriptional regulation, leading to its involvement in cancer development and progression.…”
Section: The Expression Of the Nrg1 Genementioning
confidence: 99%